Genomic and oncogenic preference of HBV integration in hepatocellular carcinoma - Zhao, Ling-Hao; Liu, Xiao; Yan, He-Xin; Li, Wei-Yang; Zeng, Xi; Yang, Yuan; Zhao, Jie; Liu, Shi-Ping; Zhuang, Xue-Han; Lin, Chuan; Qin, Chen-Jie; Zhao, Yi; et al. (Nature communications, 2016)
Hepatitis B virus (HBV) can integrate into the human genome, contributing to genomic instability and hepatocarcinogenesis. Here by conducting high-throughput viral integration detection and RNA sequencing, we identify 4,225 HBV integration events in tumour and adjacent non-tumour samples from 426 patients with HCC. We show that HBV is prone to integrate into rare fragile sites and functional genomic regions including CpG islands. We observe a distinct pattern in the preferential sites of HBV integration between tumour and non-tumour tissues. HBV insertional sites are significantly enriched in the proximity of telomeres in tumours. Recurrent HBV target genes are identified with few that overlap. The overall HBV integration frequency is much higher in tumour genomes of males than in females, with a significant enrichment of integration into chromosome 17. Furthermore, a cirrhosis-dependent HBV integration pattern is observed, affecting distinct targeted genes. Our data suggest that HBV integration has a high potential to drive oncogenic transformation. Hepatitis B infection is a risk factor for hepatocellular carcinoma. Here, the authors characterise viral infection in a cohort of hepatocellular carcinoma patients and find viral integration is more frequent in males than females.